Focal point a proven system to simplify your life, double your productivity, and achieve all your goals - Tracy, Brian (New York AMACOM, 2002)
Outlines the secret of high achievement: knowing how to find one's focal point--the one thing to do, at any given moment, to get the best possible results in each area of one's life. This guide helps readers analyze their lives in seven key areas and shows them how to develop goals and plans in each.
Introduction -- Unlock your full potential -- Double your productivity -- Simplify your life -- Tap your most precious resource -- Practice personal strategic planning -- Supercharge your business and career -- Improve your family and personal life -- Achieve financial independence -- Enjoy superb health and fitness -- Become everything you are capable of becoming -- Make a difference in your community -- Spiritual development and inner peace -- Seven lessons for the twenty-first century -- Focal point advanced coaching and mentoring program -- Appendix: List of values -- Recommended reading -- Index -- About the author.
Includes bibliographical references (p. 209-211) and index.
Keywords: Success -- Psychological aspects